Thermoplastic silicone elastomers from divanillin crosslinkers in a catalyst-free process. Issue 15 (13th July 2021) - Bui, Robert; Brook, Michael A.
Abstract : Silicone elastomers are typically thermosets that are difficult to recycle or repurpose. Abstract : Silicone elastomers are typically thermosets that are difficult to recycle or repurpose. Thermoplastic silicone elastomers formed from Schiff bases utilize crosslinkers based on petroleum. Vanillin is an aromatic phenolic aldehyde recovered from lignin. We demonstrate that its dimer, divanillin, formed by oxidative coupling using an Fe II/III catalytic process, serves as an effective crosslinker for telechelic and pendent aminopropylsilicones. Pendent-derived elastomers swell in solvents and exhibit dynamic adhesion at their interfaces, but are otherwise relatively intractable, essentially thermosets, due to the combination of Schiff base and H-bonding crosslinks. The elastomers derived from telechelic polymers, by contrast, are thermoplastic; chain extension through Schiff bases is accompanied by H-bonding crosslinking that is readily overcome by either solvents or heat. The silicone starting polymers are readily recovered.